Information Systems Outsourcing Towards Sustainable Business Value - Hirschheim, Rudy.; Heinzl, Armin; Dibbern, Jens.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book attempts to synthesize research that contributes to a better understanding of how to reach sustainable business value through information systems (IS) outsourcing. Important topics in this realm are how IS outsourcing can contribute to innovation, how it can be dynamically governed, how to cope with its increasing complexity through multi-vendor arrangements, how service quality standards can be met, how corporate social responsibility can be upheld, and how to cope with increasing demands of internationalization and new sourcing models, such as crowdsourcing and platform-based cooperation. These issues are viewed from either the client or vendor perspective, or both. The book should be of interest to all academics and students in the fields of Information Systems, Management, and Organization as well as corporate executives and professionals who seek a more profound analysis and understanding of the underlying factors and mechanisms of outsourcing.
Introduction -- Part I: Innovation Management -- Part II: Governance Frames -- Part III: Dynamic Governance Adaption -- Part IV: Multi-vendor and Multi-Client Ecosystem Management -- Part V: International Growth - the Case of China -- Part VI: Social Responsibility and Social Capital Management -- Part VII: Crowdsourcing and Open Platforms.
Keywords: Economics; Management information systems; Economics/Management Science; Business Information Systems; Business Strategy/Leadership.; Information Systems Applications (incl. Internet).